2003
DOI: 10.1007/s15010-003-2069-x
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Characteristics of Escherichia coli Strains Causing Asymptomatic Bacteriuria

Abstract: Background:The objective of this study was to examine the expression of Escherichia coli virulence-associated factors among the strains isolated from a group of women with a history of recurrent urinary tract infections (UTIs), in whom asymptomatic bacteriuria (ABU) was detected at follow-up, and from a group of children without a history of previous UTI, in whom ABU was detected during the screening. Possible differences between the virulence potential of these strains were investigated. Materials and Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Colonization of urinary catheters by pathogens is a main problem among hospitalized patients, often resulting in recurrent infections. The problem is accentuated by the rise of antibiotic resistance in UTI infectious bacteria due to the spread of resistance genes (Manges et al , 2001; Vranes et al , 2003). Furthermore, when a biofilm has established in a catheter, the inherent tolerance/resistance of biofilm‐dwelling bacteria towards antibiotics often make such infections extremely recalcitrant and hard to eradicate.…”
Section: Discussionmentioning
confidence: 99%
“…Colonization of urinary catheters by pathogens is a main problem among hospitalized patients, often resulting in recurrent infections. The problem is accentuated by the rise of antibiotic resistance in UTI infectious bacteria due to the spread of resistance genes (Manges et al , 2001; Vranes et al , 2003). Furthermore, when a biofilm has established in a catheter, the inherent tolerance/resistance of biofilm‐dwelling bacteria towards antibiotics often make such infections extremely recalcitrant and hard to eradicate.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the virulence characteristics of uropathogenic E. coli (UPEC) isolates and ABU isolates, in order to get better understanding of how some UTI strains can cause severe disease, while others can be used prophylactically to prevent the same (Blanco et al 1996 ; Dobrindt et al 2003 ; Vranes et al 2003 ; Johnson et al 2005 ; Marrs et al 2005 ). ABU strains have been shown to lack many of the virulence-associated phenotypes; many of them are nonhaemolytic, nonadherent and lack haemagglutination ability (Vranes et al 2003 ). Strain 83972 lacks many of the virulence-associated phenotypes but has been shown to carry many of the virulence-associated genes, such as kps , iutA , fyuA and malX (Dobrindt et al 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although all similarities are known, there have not been any reliable studies that demonstrate the direct relationship yet. [6][7][8][9][10][11][12] Most of the studies conducted are studies including a short-term follow-up in few patient series. However, besides, there are also studies which followed for a long period of time like 14 years and concluded that it was not a risk factor for UTI.…”
Section: Introductionmentioning
confidence: 99%